Cultivo de células-tronco derivadas da polpa dentária sobre arcabouço de hidroxiapatita e fosfafo tricálcio: estudo piloto - Fonseca, Sabrina Cunha da (2018)
Mesenchymal stem cells of dental origin have demonstrated potential application in bioengineering. The study of scaffolds and stem cells has become fundamental in this field, and the study of bioceramics, especially of Hydroxyapatite (HA) and Beta Tricálcico Phosphate (βTCP), has presented important results in the application for bone reconstruction. Thus, the objective of this study was to associate in vitro the mesenchymal stem cells obtained from the deciduous tooth pulp (SHEDs) with a nanostructured HAβTCP framework. Analyzes were performed by X-ray Spectroscopy by Energy Dispersion (EDS), Scanning Electron Microscopy (SEM), and immunofluorescence at times of 24, 48 and 72 hours. It can be noticed that the calcium levels on the surface of the cells presented much higher in the association with the framework than without the same (approximate atomic average of 30% and 0.70%, respectively). The cells with the scaffold presented protuberances similar to secretory vesicles on their surface, a concentration of ions, possibly to guide their deposition. At immunofluorescence, the behavior profile was similar between the cells with and the scaffold, however, the number of nuclei and percentage of cell area was smaller with the scaffold, probably due to the migration of the cells into the scaffold and possible differentiation. Thus, new studies with replication of the conditions presented in the current study and characterization of cells with the framework become necessary. It can be concluded that the association of SHEDs with nanostructured HA-βTCP framework presented characteristics with a potential for application in advanced cellular therapy in bone reconstruction.